Social Interaction between the Bajo Sea Nomads and Local Communities in Torosiaje Village, Gorontalo, Indonesia - Darmansyah N Samahu; Funco Tanipu; Dewinta Rizky R Hatu (UNIB Press, 2026)
Social interaction plays a fundamental role in shaping social relationships and maintaining harmony within communities. This study aims to examine the patterns and forms of social interaction between the Bajo community of Torosiaje Laut and the local Gorontalo community. A qualitative descriptive approach was employed to explore the dynamics of social interaction within the community. Data were collected through observation, in-depth interviews, and documentation involving village officials, traditional leaders, members of the Bajo community, residents, and visitors. The findings reveal that social interactions between the Bajo and local Gorontalo communities are harmonious and sustainable. These interactions are reflected through several indicators of social interaction, including social contact, communication, cooperation, mutual understanding, shared perceptions, empathy, openness, and social support. Cultural differences between the two communities do not lead to social conflict; instead, they strengthen social cohesion and community integration. This study concludes that constructive social interaction plays a crucial role in maintaining social harmony and strengthening community integration in Torosiaje Village.